Respuesta :

Answer:

y= -3x +6

Step-by-step explanation:

slope-intercept form:

y=mx +c, where m is the slope and c is the y-intercept.

Given that the slope is -3, m= -3.

Susbt. m= -3 into the equation:

y= -3x +c

Since the line passes the point (4, -6),

(4, -6) lies on the line and must therefore satisfy the equation. Thus, susbt. (4, -6) into the equation to find the value of c.

y= -3x +c

when x=4, y= -6,

-6= -3(4) +c

-6= -12 +c

c= 12 -6

c= 6

Hence, the equation of the line is y= -3x +6.